Enhanced Stability and Decolorization of Coomassie Brilliant Blue R-250 by Dextran Aldehyde-modified Horseradish Peroxidase - Altikatoglu, Melda; Celebi, Mithat (INFORMA HEALTHCARE, 2011)
Horseradish peroxidase (EC 1.11.1.7) was chemically modified by periodate-activated dextran. The activities of free and modified enzyme against organic-aqueous interface and some chemicals were determined. Modified HRP remained fully active in the presence of organic solvent for 4 h. However, the unmodified enzyme lost 50% of its activity within the first 2 h. The effects of possible inhibitors on enzyme activity were investigated. In addition, Coomassie Brilliant Blue R-250 was efficiently decolorized using the free and modified HRP. After 5 minutes of treatment, the color removal of dye was 80-90%. Modified HRP showed effective performance compared to free HRP.
Keywords: HRP; dextran aldehyde; modification; Coomassie Brilliant Blue R-250; decolorization; AZO-DYE; INTERFACIAL INACTIVATION; TEXTILE; DEGRADATION; REMOVAL; OXIDASE; IMMOBILIZATION; NANOPARTICLES; TEMPERATURE; EFFLUENT; Biotechnology & Applied Microbiology; Engineering; Materials Science